211k views
0 votes
Complete the steps of the derivation of the quadratic formula step 1: (x+b/2a)^2-b^2-4ac/4a^2=0

Complete the steps of the derivation of the quadratic formula step 1: (x+b/2a)^2-b-example-1

2 Answers

6 votes

Answer:

The final solution of the quadratic equation is


x=(-b\pm√(b^2-4ac))/(2a)

Explanation:

Given : The steps of the derivation of the quadratic formula

Step 1:
(x+(b)/(2a))^2-(b^2-4ac)/(4a^2)=0

To find : Complete the steps.

Solution :

Step 1: Write the expression


(x+(b)/(2a))^2-(b^2-4ac)/(4a^2)=0

Step 2: Re-write the expression


(x+(b)/(2a))^2=(b^2-4ac)/(4a^2)

Step 3 : Square Root both side


(x+(b)/(2a))=\sqrt{(b^2-4ac)/(4a^2)}

Step 4: Simplifying we get


x+(b)/(2a)=(√(b^2-4ac))/(2a)

Step 5: Make x the subject


x=(√(b^2-4ac))/(2a)-(b)/(2a)

Therefore, The final solution of the quadratic equation is


x=(-b\pm√(b^2-4ac))/(2a)

User Hazem Alabiad
by
6.0k points
6 votes
(x+b/2a)^2-(b^2-4ac)/2a=0
Step 2:
Re-write the expression:
(x+b/2a)^2=(b^2-4ac)/4a^2

Step 3:
get the square root of both sides:
x+b/2a=sqrt[(b^2-4ac)/4a^2]

Step 4:
Simplifying we get:
x+b/2a=sqrt[b^2-4ac]/2a

Step 5
Make x the subject:
x=-b/2a+/-sqrt[b^2-4ac]/2a


User Kurtcorbett
by
6.0k points